Ectopic expression of the Drosophila Cdk1 inhibitory kinases, wee1 and myt1, interferes with the second mitotic wave and disrupts pattern formation during eye development. - Price, D.M.; Jin, Z.; Rabinovitch, S.; Campbell, S.D. (Genetics, 2002)
Wee1 kinases catalyze inhibitory phosphorylation of the mitotic regulator Cdk1, preventing mitosis during S phase and delaying it in response to DNA damage or developmental signals during G2. Unlike yeast, metazoans have two distinct Wee1-like kinases, a nuclear protein (Wee1) and a cytoplasmic protein (Myt1). We have isolated the genes encoding Drosophila Wee1 and Myt1 and are using genetic approaches to dissect their functions during normal development. Overexpression of Dwee1 or Dmyt1 during eye development generates a rough adult eye phenotype. The phenotype can be modified by altering the gene dosage of known regulators of the G2/M transition, suggesting that we could use these transgenic strains in modifier screens to identify potential regulators of Wee1 and Myt1. To confirm this idea, we tested a collection of deletions for loci that can modify the eye overexpression phenotypes and identified several loci as dominant modifiers. Mutations affecting the Delta/Notch signaling pathway strongly enhance a GMR-Dmyt1 eye phenotype but do not affect a GMR-Dwee1 eye phenotype, suggesting that Myt1 is potentially a downstream target for Notch activity during eye development. We also observed interactions with p53, which suggest that Wee1 and Myt1 activity can block apoptosis.